Interferon Lambda: A New Sword in Cancer Immunotherapy. (6th December 2011) - Lasfar, Ahmed; Abushahba, Walid; Balan, Murugabaskar; Cohen-Solal, Karine A.
Abstract : The discovery of the interferon-lambda (IFN- λ ) family has considerably contributed to our understanding of the role of interferon not only in viral infections but also in cancer. IFN- λ proteins belong to the new type III IFN group. Type III IFN is structurally similar to type II IFN (IFN- γ ) but functionally identical to type I IFN (IFN- α / β ). However, in contrast to type I or type II IFNs, the response to type III IFN is highly cell-type specific. Only epithelial-like cells and to a lesser extent some immune cells respond to IFN- λ . This particular pattern of response is controlled by the differential expression of the IFN- λ receptor, which, in contrast to IFN- α, should result in limited side effects in patients. Recently, we and other groups have shown in several animal models a potent antitumor role of IFN- λ that will open a new challenging era for the current IFN therapy.